Association between suicide death and concordance with benzodiazepine treatment guidelines for anxiety and sleep disorders - Boggs, Jennifer M.; Lindrooth, Richard C.; Battaglia, Catherine; Beck, Arne; Ritzwoller, Debra P.; Ahmedani, Brian K.; Rossom, Rebecca C.; Lynch, Frances L.; Lu, Christine Y.; Waitzfelder, Beth E.; Owen-Smith, Ashli A.; Simon, Gregory E.; et al. (General Hospital Psychiatry, 2020)
Objective: Guidelines for management of anxiety and sleep disorders emphasize antidepressant medications and/or psychotherapy as first/second-line and benzodiazepines as third-line treatments. We evaluated the association between suicide death and concordance with benzodiazepine guidelines. Methods: Retrospective case-control study of patients with anxiety and/or sleep disorders from health systems across 8 U.S. states within the Mental Health Research Network. Suicide death cases were matched to controls on year and health system. Appropriate benzodiazepine prescribing defined as: no monotherapy, no long duration, and/or age < 65 years. The association between guideline concordance and suicide death was evaluated, adjusting for diagnostic and treatment covariates. Results: Sample included 6960 patients with anxiety disorders (2363 filled benzodiazepine) and 6215 with sleep disorders (1237 filled benzodiazepine). Benzodiazepine guideline concordance was associated with reduced odds for suicide in patients with anxiety disorders (OR = 0.611, 95% CI = 0.392–0.953, p = 0.03) and was driven by shorter duration of benzodiazepine use with concomitant psychotherapy or antidepressant medication. The association of benzodiazepine guideline concordance with suicide death did not meet statistical significance in the sleep disorder group (OR = 0.413, 95% CI = 0.154–1.11, p = 0.08). Conclusions: We found reduced odds for suicide in those with anxiety disorders who filled benzodiazepines in short-moderate duration with concomitant psychotherapy or antidepressant treatment. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: Anxiety; Anxiety Disorders; Anxiety disorder; Benzodiazepine; Benzodiazepines; Death and Dying; Drug Therapy; Sleep Wake Disorders; Sleep disorder; Suicide; Treatment Guidelines